How to find fraud and corruption recipes for the aspiring fraud detective - Iyer, Nigel K. (Routledge, 2020)
In a typical working environment in which 'fraud and corruption' is as normal as a headache or as common as a cold, everyone in the organization has a role to play in finding and deterring fraudsters. Despite universal acknowledgement that these things may be illegal but still prevalent, managers still treat them as 'someone else's problem' or 'something that happens to other businesses, not ours’. This book shows, in simple terms, how everybody can become a successful fraud detective. A series of proven and easy-to-follow recipes show how to find the tell-tale signs of fraud and corruption and work with colleagues to deal with fraud smartly, keeping the organization you work for healthy and clean.